Autophagy inhibition in early but not in later stages prevents 3T3-L1 differentiation: Effect on mitochondrial remodeling - Skop, Vojtech; Cahova, Monika; Dankova, Helena; Papackova, Zuzana; Palenickova, Eliska; Svoboda, Petr; Zidkova, Jarmila; Kazdova, Ludmila (Differentiation; research in biological diversity, 2014)
Autophagy is essential for successful white adipocyte differentiation but the data regarding the timing and relevance of autophagy action during different phases of adipogenesis are limited. We subjected 3T3-L1 preadipocytes to a standard differentiation protocol and inhibited the autophagy within time-limited periods (days 0-2; 2-4; 4-6; 6-8) by asparagine or 3-methyladenine. In the normal course of events, both autophagy flux and the mRNA expression of autophagy related genes (Atg5, Atg12, Atg16, beclin 1) is most intensive at the beginning of differentiation (days 0-4) and then declines. The initiation of differentiation is associated with a 50% reduction of the mitochondrial copy number on day 2 followed by rapid mitochondrial biogenesis. Preadipocytes and differentiated adipocytes differ in the mRNA expression of genes involved in electron transport (Nufsd1, Sdhb, Uqcrc1); ATP synthesis (ATP5b); fatty acid metabolism (CPT1b, Acadl); mitochondrial transporters (Hspa9, Slc25A1) and the TCA cycle (Pcx, Mdh2) as well as citrate synthase activity. Autophagy inhibition during the first two days of differentiation blocked both phenotype changes (lipid accumulation) and the gene expression pattern, while having no or only a marginal effect over any other time period. Similarly, autophagy inhibition between days 0-2 inhibited mitotic clonal expansion as well as mitochondrial network remodeling. In conclusion, we found that autophagy is essential and most active during an initial stage of adipocyte differentiation but it is dispensable during its later stages. We propose that the degradation of preadipocyte cytoplasmic structures, predominantly mitochondria, is an important function of autophagy during this phase and its absence prevents remodeling of the mitochondrial gene expression pattern and mitochondrial network organization.
Keywords: autofagie; Adipocytes; Preadipocytes; tukové buňky; Cell Differentiation; mitochondrie; 3T3-L1 Cells; vývojová regulace genové exprese; Autophagy; Mice; adipogeneze; Gene Expression Regulation, Developmental; Asparagine; 3T3-L1 cells; zvířata; Differentiation; myši; buňky 3T3-L1; Mitochondria; buněčná diferenciace; asparagin; Adipogenesis; Animals